Scaling severe acute malnutrition treatment with community health workers: a geospatial coverage analysis in rural Mali - Pilar Charle-Cuéllar; Lidia Espí-Verdú; Juan Goyanes; Magloire Bunkembo; Salimata Samake; Mamadou Traore; Adama Balla Coulibaly; Aly Landouré; Fatou Diawara; Abdias Ogobara Dougnon; Antonio Vargas; Noemí López-Ejeda (BMC, 2022)
Abstract Background In 2015, the Ministry of Health in Mali included the treatment of severe acute malnutrition (SAM) into the package of activities of the integrated Community Case Management (iCCM). This paper aims to analyze the impact of including community health workers (CHWs) as treatment providers outside the Health Facilities (HFs) on the coverage of SAM treatment when scaling up the intervention in the three largest districts of the Kayes Region in Mali. Methods A baseline coverage assessment was conducted in August 2017 in the three districts before the CHWs started treating SAM. The end-line assessment was conducted one year later, in August 2018. Coverage was assessed by the standardized methodology called Semi-Quantitative Evaluation of Access and Coverage (SQUEAC). The primary outcome was treatment coverage and other variables evaluated were the geographical distribution of the HFs, CHW's sites and overlapping between both health providers, the estimation of children with geographical access to health care and the estimation of children screened for acute malnutrition in their communities. Results Treatment coverage increased in Kayes (28.7-57.1%) and Bafoulabé (20.4-61.1%) but did not in Kita (28.4-28.5%). The decentralization of treatment has not had the same impact on coverage in all districts, with significant differences. The geospatial analyses showed that Kita had a high proportion of overlap between HFs and/or CHWs 48.7% (39.2-58.2), a high proportion of children without geographical access to health care 70.4% (70.1-70.6), and a high proportion of children not screened for SAM in their communities 52.2% (51.9-52.5). Conclusions Working with CHWs in SAM increases treatment coverage, but other critical aspects need to be considered by policymakers if this intervention model is intended to be scaled up at the country level. To improve families' access to nutritional health care, before establishing decentralized treatment in a whole region it must be considered the geographical location of CHWs. This previous assessment will avoid overlap among health providers and ensure the coverage of all unserved areas according to their population densities need. Trial registration: ISRCTN registry with ID 1990746. https://doi.org/10.1186/ISRCTN14990746